ISSUES FACING ISLAMIC MICROFINANCE AND THEIR POSSIBLE SOLUTIONS: EMPIRICAL EVIDENCE FROM AMANAH IKHTIAR MALAYSIA - Kassim, Salina; Hassan, Rusni (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Microfinance has become a widely accepted tool for poverty alleviation and being included in the national development agenda in many countries throughout the globe. It has served as an effective method to improve financial inclusion by increasing the access to finance to specific groups of the society who are often being marginalized by the mainstream finance, especially women micro-entrepreneurs and the poor. Despite this, microfinance continues to face various issues and challenges that hinder its effective functioning, resulting in many microfinance institutions (MFIs) to operate at sub-optimal level, thus fail to achieve their objectives. This study attempts to discern the issues and challenges facing the Islamic MFIs by focusing on the experience of Amanah Ikhtiar Malaysia (AIM), one of the world’s largest Islamic MFIs, and subsequently propose possible solutions to address those issues. In methodology, the study conducts a survey questionnaire regarding potential issues and challenges of Islamic microfinance on 402 women micro-entrepreneurs who are currently clients of several AIM centres in Hulu Selangor. In efforts to get enriching insights, we further relate those issues with the demographic profile of the clients. Findings of this study provide new insights into the issues and challenges facing the women micro-entrepreneurs based on their direct experiences, and consequently relevant suggestions can be provided in addressing these issues facing the clients of the Islamic microfinance industry.